2013
DOI: 10.1002/pon.3370
|View full text |Cite
|
Sign up to set email alerts
|

Wearing my heart on my chest: dating, new relationships, and the reconfiguration of self-esteem after breast cancer

Abstract: The process of dating and starting a new intimate relationship had the potential to restore women's self and bodily esteem previously diminished by breast cancer. The reconfiguration of self-esteem following breast cancer is thus experienced as an ongoing process that begins with diagnosis and continues well into the new relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 41 publications
3
29
1
Order By: Relevance
“…Many un‐partnered women report a strong desire to begin romantically “dating” (ie, meeting with someone with whom they have a romantic interest) following breast cancer treatment, in the hope of forming a new relationship . However, these women also report high levels of dating anxiety, that is, worry about dating situations and fear of negative evaluation by romantic partners . Some women also report difficulties with interpersonal skills required when dating, including initiating relationships and disclosing personal information to potential partners …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many un‐partnered women report a strong desire to begin romantically “dating” (ie, meeting with someone with whom they have a romantic interest) following breast cancer treatment, in the hope of forming a new relationship . However, these women also report high levels of dating anxiety, that is, worry about dating situations and fear of negative evaluation by romantic partners . Some women also report difficulties with interpersonal skills required when dating, including initiating relationships and disclosing personal information to potential partners …”
Section: Introductionmentioning
confidence: 99%
“…However, these women also report high levels of dating anxiety, that is, worry about dating situations and fear of negative evaluation by romantic partners . Some women also report difficulties with interpersonal skills required when dating, including initiating relationships and disclosing personal information to potential partners …”
Section: Introductionmentioning
confidence: 99%
“…The issues faced by these women were the subject of a study conducted by Kurowecki and Fergus, in which 15 breast cancer survivors who were either actively dating or in a new relationship following their index cancer diagnosis were interviewed [76]. The major themes described by these women included (a) extreme vulnerability related to the diagnosis of breast cancer, (b) their obligation to disclose their cancer history, and (c) the importance of the new relationship in helping re-establish a new sense of self.Their findings indicate that even for women who are not in stable relationships, new and future partnerships can be an important aspect of recovery toward a new normal.…”
Section: Nonendocrine Therapiesmentioning
confidence: 99%
“…Most individuals disclosed their terminal illnesses as means of receiving support and help from others while at the same time tried to regain a sense of self-esteem and control over their unfavourable circumstances. Kurowecki and Fergus found that women with breast cancer disclosed their diagnosis to their partners when they were in a newly committed relationship or during the dating process [7]. In doing so, the women were slowly reclaiming their sense of self and bodily esteem as well as evaluating the reaction of their partners towards their diagnosis before deciding whether to proceed further with the relationship further.…”
Section: Disclosure Of Illnessmentioning
confidence: 99%